Modulating the RFamide-related peptide-3/G protein-coupled receptor 147 signaling pathway with nourishing Yin-removing fire herbal mixture to alleviate precocious puberty in female rats: An experimental study - Xiaoli Dai; Yuanyuan He; Suhuan Li; Yanyan Sun; Wen Sun; Zhanzhuang Tian; Ph.D; Jian Yu; Ph.D; Nurgul Ablakimova; Yonghong Wang (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Precocious puberty (PP) involves early activation of the hypothalamic gonadotropin-releasing hormone (GnRH) generator. The RFamide-related peptide/G protein-coupled receptor 147 (RFRP3/GPR147) signaling pathway is vital in inhibiting GnRH and delaying puberty onset. The nourishing Yin-removing fire (NYRF) herbal mixture has shown promising results in treating PP. Objective: This study aimed to assess the impact of the NYRF herbal mixture on the RFRP3/GPR147 signaling pathway in the hypothalamus and its potential in alleviating PP in female rats. Materials and Methods: In a controlled experiment, 24 female Sprague-Dawley rats (11.20 ± 0.69 gr, postnatal day [PD5]) were divided into normal, model, normal saline, and NYRF groups (n = 6/each). PP was induced in the model, normal saline, and NYRF groups by subcutaneous injection of danazol at PD5. The NYRF herbal mixture or normal saline was administered from PD15. Serum sex hormone levels and hypothalamic samples were collected for mRNA and protein expression at PD30. Results: In the model group, hypothalamic GnRH and kisspeptin levels increased, while RFRP3 and GPR147 levels decreased, luteinizing hormone levels elevated, reproductive organ coefficients increased, and the vagina opened earlier compared to the normal group. Conversely, the NYRF group exhibited lower GnRH and kisspeptin levels but higher RFRP3 levels in the hypothalamus. Serum luteinizing hormone levels were reduced, reproductive organ coefficients were reduced, and the vaginal opening was delayed compared to the model and normal saline groups. Conclusion: The NYRF herbal mixture delayed sexual development in rats with PP by hypothalamic upregulating RFRP3 and downregulating GnRH and kisspeptin.